Training loads of 12-year-old players of the student club «Żabianka Gdańsk» - Filipkowska, Dominika; Tsyhanovska, Nataliia; Kreft, Paulina; Skalski, Dariusz W.; Kindzer, Bogdan (My University, 2025)
Background and Study Aim.Training load management is a key element of modern competitive swimming, particularly during early stages of long-term athlete development. Proper distribution of training volume and the application of tapering strategies are essential for optimizing performance while minimizing excessive fatigue and the risk of overtraining in young athletes. Previous studies have emphasized the importance of progressive load increase and systematic load reduction prior to major competitions; however, empirical data describing training load structures in young competitive swimmers remain limited. The aim of the study was to analyze the distribu-tion of training loads during a training macrocycle and the direct pre-competition period in young swimmers and to examine their association with competitive performance outcomes. It was hypothesized that a gradual increase in training volume followed by a systematic reduction before the main competition would support performance improvement in swimmers aged 11–12 years.Material and methods.Thirteen competitive swimmers (7 girls and 6 boys), aged 11–12 years, from the UKS Żabianka Gdańsk swimming club participated in the study. All athletes trained regularly and competed in official swimming events. Training load distribution was analyzed over a seven-month macrocycle (September 2024–March 2025), with particular attention paid to the four-week period preceding the main competition. Training volume was quantified based on swimming distance completed during training sessions. Competition performance data were obtained from officially recorded race results available in the swimrankings.net database. Descriptive statistical methods were applied, and training load trends were presented using line and bar graphs.Results.Training volume demonstrated a gradual increase throughout the macrocycle, reaching its highest val-ues in the final preparatory phase. During the four-week pre-competition period, a systematic reduction in train-ing volume was observed. Competitive performance analysis indicated improvements in race times across differ-ent swimming strokes and distances, including sprint and middle-distance events. Performance enhancement was observed in both male and female swimmers following a unified training program.Conclusions.The results indicate that progressive training volume increase during the macrocycle combined with systematic load reduction before the main competition represents an effective preparation model for young swimmers. This approach supports performance development while aligning with principles of long-term athlete development. Future research should include internal load indicators to provide a more comprehensive assess-ment of training responses in youth swimming.

Поєднання прогресивного збільшення тренувального обсягу в межах макроциклу та його цілеспрямованого зниження у безпосередньому підготовчому періоді є ефективною моделлю підготовки юних плавців. Такий підхід відповідає принципам багаторічної підготовки спортсменів і створює передумови для стабільного спортивного розвитку. Подальші дослідження доцільно спряму
Keywords: фізичні тренування; плавання; resistance; swimming; training stages